A new method for analysis and design of iterative learning control algorithms in the time-domain. (December 2016) - Zsiga, Norbert; Dooren, Stijn van; Elbert, Philipp; Onder, Christopher H.
Abstract: In this paper, a novel analysis method for iterative learning control (ILC) algorithms is presented. Even though expressed in the lifted system representation and hence in the time-domain, the convergence rate as a function of the frequency content of the error signal can be determined. Subsequently, based on the analysis method, a novel ILC algorithm (F-ILC) is proposed. The convergence rate at specific frequencies can be set directly in the design process, which allows simple tuning and a priori known convergence rates. Using the F-ILC design, it is shown how to predict the required number of iterations until convergence is achieved, depending on the reference trajectory and information on the system repeatability. Numerical examples are given and experimental results obtained on an internal combustion engine test bench are shown for validation. Abstract : Highlights: An analysis method for ILC algorithms is presented that gives an insight into the frequency dependent convergence rate. A novel ILC algorithm is proposed, where the convergence rate at specific frequencies can be set directly for simple tuning. Experimental results validate the effectiveness of the proposed learning algorithm as well as the easy adjustability. This algorithm gives the possibility to specify the convergence rate for single frequencies individually and independently.